‘The Kindly Fruits of the Earth’: The Materiality of the Cornhill Magazine (1860) - Simon Cooke (Cahiers Victoriens et Edouardiens)
The illustrated texts appearing in The Cornhill Magazine have been the subject of detailed investigation. The composite novels of Trollope, Thackeray, Eliot, and Reade have been examined at length, and recent commentators have assessed the importance of the designs’ physical placement. However, other aspects of The Cornhill’s material form have received less attention. This article argues that the editor and publisher used the magazine’s physical presentation to position it in relation to its diverse audiences and helped to establish its reputation as the foremost literary journal of its time. The analysis considers several key issues: the transmission of value systems through the medium of the symbolic cover; the significance of advertisements; the journal’s physical dimensions; the mode of industrialized production; and the role of the two-fold issue, which differentiated between male and female audiences. My analysis views these elements as part of a sophisticated branding, which generated a range of meanings for the original consumers and engaged, in particular, with important issues of gender and class. My intention is to recover those cultural meanings, enshrined in a grammar of physical signs, as they operated in the 1860s.